2016
DOI: 10.1162/jocn_a_00895
|View full text |Cite
|
Sign up to set email alerts
|

Pupil Diameter Tracks the Exploration–Exploitation Trade-off during Analogical Reasoning and Explains Individual Differences in Fluid Intelligence

Abstract: Abstract■ The ability to adaptively shift between exploration and exploitation control states is critical for optimizing behavioral performance. Converging evidence from primate electrophysiology and computational neural modeling has suggested that this ability may be mediated by the broad norepinephrine projections emanating from the locus coeruleus (LC) [Aston-Jones, G., & Cohen, J. D. An integrative theory of locus coeruleus-norepinephrine function: Adaptive gain and optimal performance. Annual Review of Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 46 publications
8
47
0
Order By: Relevance
“…These changes in pupil baseline levels and pupil dilations were short-lived. Our findings extend previous studies that found similar pupil changes when people disengaged from (and restarted) an auditory discrimination task (Gilzenrat et al, 2010), when people shifted between multiple bandit gambling machines (Jepma & Nieuwenhuis, 2011) and when people shifted between strategies in solving Raven's Matrices (Hayes & Petrov, 2016). By contrast to these previous studies, in our research, participants chose between two motivationally different tasks-namely an effortful, but profitable 2-back (labor) and an effortless, but unprofitable attractiveness rating task (leisure).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These changes in pupil baseline levels and pupil dilations were short-lived. Our findings extend previous studies that found similar pupil changes when people disengaged from (and restarted) an auditory discrimination task (Gilzenrat et al, 2010), when people shifted between multiple bandit gambling machines (Jepma & Nieuwenhuis, 2011) and when people shifted between strategies in solving Raven's Matrices (Hayes & Petrov, 2016). By contrast to these previous studies, in our research, participants chose between two motivationally different tasks-namely an effortful, but profitable 2-back (labor) and an effortless, but unprofitable attractiveness rating task (leisure).…”
Section: Discussionsupporting
confidence: 89%
“…In sum, building on our findings and on recent insights in NE function, it is possible that previous experiments about shifts from exploitation to exploration (Gilzenrat et al, 2010;Hayes & Petrov, 2016;Jepma & Nieuwenhuis, 2011;Kane et al, 2017;Pajkossy et al, 2017) observed NE facilitating the execution of task switching, rather than NE facilitating motivational shifts. By contrast to these previous studies, our paradigm used two qualitatively distinct tasks, with distinct motivational properties (i.e., labor vs. leisure).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Across different tasks (Stafford & Dewar, 2015;Hayes & Petrov, 2015;Gureckis & Love, 2009), humans show variable behavioural strategies, with initial exploration of possible responses and later exploitation of efficient ones. From computer gaming to analogical reasoning and decision making, it has been shown that participants who initially show more diversity across trials (and possibly commit more errors) show better overall performance.…”
Section: Discussionmentioning
confidence: 99%
“…First, van Ravenzwaaij, Brown, and Wagenmakers (2011) showed that the speed of information processing (i.e., Òdrift rateÓ from the Diffusion Model: Ratcliff, 1978;and Ratcliff, Schmiedek, & McKoon, 2008), correlates well with the reaction timeÕs standard deviation and somewhat less consistently with its mean (see also Baumeister, 1998). Second, Stafford and Dewar (2014) reported that game players who exhibit greater initial variability in performance achieved a higher overall score, and explained this pattern in terms of the exploration/exploitation trade-off (for similar results in other domains see Stafford et al, 2012;Gureckis & Love, 2009;Hayes & Petrov, 2015). By combining the findings of Stafford and Dewar (2014) and van Ravenzwaaij, Brown, and Wagenmakers (2011) with our two measures of individual differences in speed we are in a position to hypothesize that (a) an individualÕs processing speed will be indicated by their deviations, both in average speed and in the change in speed; and that (b) a positive change in speed (i.e., acceleration) may disguise more variable performance at the beginning of the experiment, in order to explore and then exploit rewarding behaviour at a later point in time.…”
Section: Individual Differences In Readingmentioning
confidence: 94%